Ship squat in non-uniform water depth - Gourlay, Tim (Coasts and Ports Australasian Conference, 2013)
The problem of predicting ship squat in non-uniform water depth is studied in this paper. For transverse depth variations, calculations are done using slender-body shallow-water theory, as implemented in the code “ShallowFlow”. Examples are given for realistic ships transiting dredged channels, and the effect of channel width on ship squat is discussed. Further examples are given for ships transiting canals such as the new Panama Canal. It is found that in a typical dredged channel, midship squat can be in the order of 20% larger than in open water of the same depth, while dynamic trim is essentially unchanged. In canals such as the new Panama canal, midship sinkage can be 100% larger than in open water of the same depth.